The Parkinson’s Disease Composite Scale Is Adequately Responsive to Acute Levodopa Challenge - Dávid Pintér; Pablo Martinez-Martin; József Janszky; Norbert Kovács (Parkinson's Disease)
Background. The Parkinson’s Disease Composite Scale (PDCS) is a recently developed easy-to-use tool enabling a timely but comprehensive assessment of Parkinson’s disease (PD)-related symptoms. Although the PDCS has been extensively validated, its responsiveness to acute levodopa challenge has not been demonstrated yet. Objective. To investigate the correlation between changes in the motor examination part of the Movement Disorder Society-sponsored Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and the PDCS motor scores during acute levodopa challenge and calculate a cutoff range on the PDCS indicating clinically relevant improvement. Methods. A consecutive series of 100 patients with parkinsonism were assessed using the motor examination sections of the MDS-UPDRS and the PDCS at least 12 hours after the last levodopa dose and after the administration of a single dose of a suprathreshold immediate formulation of levodopa/benserazide reaching the “best ON.” Results. There was a high correlation between changes in the MDS-UPDRS and the PDCS motor scores (Spearman’s rho = 0.73, p<0.001). Receiver operating characteristic analysis revealed that a 14.6%–18.5% improvement in the PDCS motor scores corresponds to a 20–30% improvement in the MDS-UPDRS motor examination. Conclusions. The PDCS can reliably and adequately respond to an acute levodopa challenge. Any improvements in PDCS motor scores exceeding the 14.6–18.5% threshold could represent a clinically relevant response to levodopa.